Dynamics of Glucose Metabolism After Kidney Transplantation - Martina Guthoff; Robert Wagner; Karoline Weichbrodt; Silvio Nadalin; Alfred Königsrainer; Hans-Ulrich Häring; Andreas Fritsche; Nils Heyne (Karger Publishers, 2017)
Background/Aims: Posttransplantation diabetes mellitus (PTDM) impacts patient and allograft survival after kidney transplantation. Prediabetes, which is an independent risk factor for PTDM, is modifiable also in a post-transplant setting. Understanding the risks and dynamics of impaired glucose metabolism after transplantation is a key component for targeted intervention. Methods: A retrospective chart analysis of all adult non-diabetic renal allograft recipients (n=251, 2007-2014) was performed. Longitudinal follow-up included fasting plasma glucose and HbA1c, as well as data on allograft function and immunosuppression at consecutive time points (months 3-6 to >5 years post transplantation). Results: Throughout follow-up, median prevalence of prediabetes and PTDM was 53.3 [52.4-55.7]% and 15.4 [15.0-16.5]%, respectively. Continuously high fluxes between states of glucose metabolism, with individual patients' state deteriorating or improving over time, resulted in a high number of incident patients even long after transplantation. The greatest number of patients shifted between normal glucose tolerance and prediabetes, followed by those between prediabetes and PTDM. Conclusion: Prediabetes and PTDM are highly prevalent after kidney transplantation and incidences remain relevant throughout follow-up. Patient fluxes into and out of the prediabetic state show that glucose metabolism is highly dynamic after transplantation. This provides a continuous opportunity for intervention in an aim to reduce diabetes-associated complications.